An update on ACE2 amplification and its therapeutic potential. (17th June 2020) - Marquez, Alonso; Wysocki, Jan; Pandit, Jay; Batlle, Daniel
Abstract: The renin angiotensin system (RAS) plays an important role in the pathogenesis of variety of diseases. Targeting the formation and action of angiotensin II (Ang II), the main RAS peptide, has been the key therapeutic target for last three decades. ACE‐related carboxypeptidase (ACE2), a monocarboxypeptidase that had been discovered 20 years ago, is one of the catalytically most potent enzymes known to degrade Ang II to Ang‐(1‐7), a peptide that is increasingly accepted to have organ‐protective properties that oppose and counterbalance those of Ang II. In addition to its role as a RAS enzyme ACE2 is the main receptor for SARS‐CoV‐2. In this review, we discuss various strategies that have been used to achieve amplification of ACE2 activity including the potential therapeutic potential of soluble recombinant ACE2 protein and novel shorter ACE2 variants.